Bioactive Volatile Compounds Of Three Medicinal Plants From Nepal - Gyawali, Rajendra; Kim, Kyong-Su (Kathmandu University Journal of Science, Engineering and Technology, 2012)
The volatile organic compounds of Asparagus racemosus, Bergenia ciliate and Terminalia chebula were isolated by simultaneous distillation–extraction (SDE) technique and then analyzed by gas chromatography–mass spectrometry (GC-MS). A total of 55, 48 and 56 compounds were identified from and compounds camphor, borneol, capric acid, furfural, myrtanal, α-pinene, α-terpeniol, perillaldehyde, 2-carene, butyrophenones, furfural, β-caryophyllene, 2-nitropropane were detected as a bioactive compounds with various proportions among the studied plants. DOI: http://dx.doi.org/10.3126/kuset.v8i1.6043 KUSET 2012; 8(1): 51-62